The Influence of Organizational Leadership to Enterprise Risk Management - Lara Rose P. Simbulan; Dr. Juliana M. Laraya (HM Journals, 2022)
Enterprise Risk Management assists organizations in reducing potential risk; it is a strategic approach to control the risk that the business may face. The main objective of this study was to determine the influence of organizational leadership on the implementation of enterprise risk management in Toms World Philippines. An assessment was conducted to determine the influence of organizational leadership on the implementation of control activities in the organization. The study was based on descriptive research design involving a quantitative approach. Data gathered were processed statistically using the SPSS by the Centro Escolar University Data Processing Center, and presented using the percentage, frequency distribution, mean, standard deviation and Pearson correlation analysis. The overall analysis revealed that the relationship between the extent of the implementation of enterprise risk management control activities and organizational leadership of Toms World Philippines was significant. However, the implementation of enterprise risk management in the organization and organization leadership can be further improved by a thorough application of the policies and procedures in controlling threats to the organization. There is a significant relationship between the organizational leadership in the implementation of enterprise risk management of Toms World Philippines. It recommends that other researchers along the field can look into the conduct of similar studies that would highlight the implementation of Enterprise Risk Management.